1997
DOI: 10.1017/s0950268897008285
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of foot-and-mouth disease type O viruses isolated in Saudi Arabia between 1983 and 1995

Abstract: Partial nucleotide sequence of the capsid polypeptide coding gene 1D (VP1) was determined for 68 serotype O foot-and-mouth disease viruses isolated between 1983 and 1995 from outbreaks occurring in Saudi Arabia. The sequences were compared with previously published sequences: 14 viruses of Middle Eastern origin (isolated between 1987 and 1991); and with four vaccine virus strain sequences, three originating from the Middle East (O1/Turkey/Manisa/69, O1/Sharquia/Egypt/72 and O1/Israel/2/85) and one from Europe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…Among the different attempts to improve the immunogenicity of these peptides, its expression as part of the hepatitis B core structure was the most promising [54]. In 1986, DiMarchi et al [70] reported protection to viral challenge in cattle immunised with a peptide in which the amino acids of the G-H loop were co-linearly synthesised with those corresponding to the carboxy terminus of VP1 (residues [200][201][202][203][204][205][206][207][208][209][210][211][212][213]. The induction of significant levels of heterologus protection in the guinea-pig with this tandem peptide has also been reported [73].…”
Section: Peptide Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the different attempts to improve the immunogenicity of these peptides, its expression as part of the hepatitis B core structure was the most promising [54]. In 1986, DiMarchi et al [70] reported protection to viral challenge in cattle immunised with a peptide in which the amino acids of the G-H loop were co-linearly synthesised with those corresponding to the carboxy terminus of VP1 (residues [200][201][202][203][204][205][206][207][208][209][210][211][212][213]. The induction of significant levels of heterologus protection in the guinea-pig with this tandem peptide has also been reported [73].…”
Section: Peptide Vaccinesmentioning
confidence: 99%
“…3) and it allows derivation of informative phylogenetic comparisons [145]. Its analysis has provided a considerable amount of information for type O, A, C, Asia, SAT 1 and SAT 2 serotypes [63,144,173,210,211,246]. The OIE/FAO World Reference Laboratory for foot-and-mouth disease, at Pirbright, UK edits a web page in which an FMDV sequence data base is available (http://www.iah.bbsrc.ac.uk/virus/ Picornaviridae/aphthovirus/fmdv.htm).…”
Section: Diagnosis and Viral Characterisationmentioning
confidence: 99%
“…We used nucleotide sequences acquired directly from specimens to circumvent any genetic changes associated with cell culture or animal adaptation [6]. It is generally accepted that FMD viruses are closely related to each other if the sequence variations of the 3' end of the 1D gene are less than 5% [12,16]. A nucleotide sequence divergence of the 3' end of the 1D gene was 0 to 3.8% among 7 Korean strains of the FMD virus, determined by the MegAlign program.…”
Section: Surveillance Of Fmdmentioning
confidence: 99%
“…In order to improve epidemiological trace of infectious agents, comparison of nucleotide sequences within a limited region of the genome has been used. In studies on FMDV molecular epidemiology, nucleotide sequencing of the partial 3' end of the 1D (VP1) gene and phylogenetic analysis have widely been utilized [5,12,13,16,18,21]. The aim of the study was to determine the genetic relatedness of Korean field strains of FMD virus obtained from 7 farms in 5 geographical locations prevailed during the spring 2000.…”
mentioning
confidence: 99%
“…In addition, and for practical reasons, sequencing of the 200-250 nt from the 3' end of the VP1 gene -either from viral RNA or, more recently, from RT-PCR amplified cDNAs -has become a complement to the serology in the characterisation of field isolates. In this way, a significant amount of information is available for type O, A, C, Asia and SAT 1 and 2 serotypes [6,21,27,34,35]. However, a detailed analysis of the informative content of this region in viruses of different serotypes, with respect to the whole VP1 gene, has not been performed.…”
Section: Introductionmentioning
confidence: 99%